Globalization versus Localization: The New Management Paradigm of 21th Century - I. V. Boiko (Управленческое консультирование)
The 21th century challenges and the erosion of the global economic and business networks makes it urgent the rethinking of the main scientific research discourse in management. The article provides the overview of the scientific publications, dedicated to the globalization of the world economy and the main causes of the upcoming deglobalization. It is highlighting the impact of the strengthening trade and techno nationalism as well as the COVID-19 pandemic consequences on the world economy in general and the creation of global value chains in particular. It is also explains the imperative of economic and business processes localization by the degradation of the global environment and climate change. Some authors state that the new theoretical mainstream and a paradigm of management is needed to reflect the realities of the substantial transitions in the global economy.